Oxidative stress alters the therapeutic effects of ketorolac in the chicks model - Abdulah, Rafal L; Mousa, Yaareb J (Vojenské zdravotnické listy, 2024)
The purpose of the research consisted of assessing the modification produced by hydrogen peroxide (H2O2)-induced oxidative stress (OS) on the ketorolac therapeutic effects in the chickens which are the analgesic, antipyretic, and anti-inflammatory. A significant decrease in the total antioxidant capacity (T-AOC) and subsequent occurrence of OS was observed in the stressed (H2O2) group on days 7th, 10th, and 14th by 39, 29, and 41%, respectively in comparison to the control (non-stressed) group. The analgesic effect of ketorolac in the stressed group had more intense in comparison to the non-stressed group, the analgesic effectiveness of ketorolac raised by 16% in that group. In the non-stressed and stressed groups, ketorolac produces its antipyretic effect at 3 and 4 hours after fever induction by baker's yeast while it shows the effect significantly at 1, 2, and 4 hours. Furthermore, ketorolac has the superiority of antipyretic action in stressed group over the non-stressed group. Ketorolac carries out anti-inflammatory activity in the stressed and non-stressed groups by 61 and 75%, respectively. Ketorolac has a significant anti-inflammatory property in the stressed group through a significant decrease in the delta thickness compared to the non-stressed group. The stressed group was treated with ketorolac for five consecutive days signifi-cantly affect the kidney and liver function concerning the non-stressed group. The net findings proposed the ability of H2O2-induced OS to alter ketorolac's analgesic, antipyretic, and anti-inflammatory properties in the chickens thus, it is recommended to reduce the dose of ketorolac intended to be given to stressed animals involved.
Keywords: analgetika; Models, Animal; Oxidative Stress; antipyretika; Statistics as Topic; Antipyretics; Anti-Inflammatory Agents, Non-Steroidal; kur domácí; oxidační stres; Animals; Ketorolac; ketorolak; modely u zvířat; statistika jako téma; zvířata; Chickens; antiflogistika nesteroidní; Analgesics